ACS Admissions in COVID-19 Outbreak: A Long-way back to Normality - Trabattoni, Daniela; Montorsi, Piero; Gili1, Sebastiano; Teruzzi, Giovanni; Baldi, Giulia Santagostino; Galli, Stefano; Fabbiocchi, Franco; Bartorelli, Antonio L. (Cardiology and Cardiovascular Medicine, 2021)
Background: The pandemic spread of the COVID-19 pneumonia caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) lead to severe social containing measures in Italy. We evaluated changes in hospitalization rates for acute coronary syndromes (ACS) during SARS-CoV-2 outbreak compared to both intra-year and inter-year control periods. Methods: ACS-related hospitalization rates at the Centro Cardiologico Monzino in Milan were retrospectively assessed during SARS-CoV-2 outbreak. The timespan from the first confirmed case of SARS-CoV-2 in Italy and lockdown ending (February 21-May 3, 2020) was the case-period (epidemic peak period). Hospitalization rates of the case-period and two control periods, one preceding (January, 1- February 20, 2020) the epidemic outbreak and the other following the end of lockdown (May 3-June 30, 2020) were analyzed and compared to same inter-year (2019) control periods. Results: 183 ACS patients were included: 80 in the case-period; and 103 in the two intra-year control periods (33 pre-case period and 70 post-case period, respectively) and compared to same periods of the previous year. ACS-related hospitalization rate was significantly higher in the case period compared to previous year, mainly driven by an increase in ST- and non-ST-elevation MI. Conclusions: ACS-related hospitalizations dramatically increased after SARS-CoV-2 outbreak onset and consequential restrictive measures, conversely to early pandemic phase observations leading to a significant decrease in emergency room accesses led by citizens’ fear of viral infection.